1987
DOI: 10.1093/bja/59.4.482
|View full text |Cite
|
Sign up to set email alerts
|

Cannulation of the Radial and Dorsalis Pedis Arteries

Abstract: The complications inherent in cannulation of the radial (group I) and dorsalis pedis (group II) arteries were studied in 46 patients. All the local and systemic variables which might be considered to contribute to damage of the artery were studied, from which it appeared that only the duration of cannulation, prothrombin time and partial thromboplastin time were significant in determining post-cannulation blood flow. A 20-gauge Teflon cannula was used in all patients and velocity of flow measured with a Dopple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 18 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…The radial artery is the most common site for arterial cannulation, and the studies that reported complication rates are listed in Table 1 [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The most common complication was temporary occlusion of the artery, the incidence of which ranged from 1.5% [ 17 ] to 35% [ 10 ] (mean 19.7%), the variability being due to the different methods employed and the degree of effort invested in detecting this complication.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The radial artery is the most common site for arterial cannulation, and the studies that reported complication rates are listed in Table 1 [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The most common complication was temporary occlusion of the artery, the incidence of which ranged from 1.5% [ 17 ] to 35% [ 10 ] (mean 19.7%), the variability being due to the different methods employed and the degree of effort invested in detecting this complication.…”
Section: Resultsmentioning
confidence: 99%
“…The dorsal pedis artery has also been cannulated without any major complications [ 24 , 54 ]. However, because of its distance from the central circulation and associated difficulties in hypotensive patients it is generally avoided [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time to onset of occlusion varied and sometimes occurred after removal of the catheter. For example, in a study of 46 human patients with catheterization of the radial or dorsal pedal arteries for elective surgery, complete occlusion was identified in six patients, in which occlusion occurred 24 hours after the catheter was removed in two patients, and not until 72 hours later in four patients . In another study of 100 human patients with radial artery catheterization and undergoing heart surgery, one patient with normal arterial blood flow after catheter removal developed occlusion 2 days later .…”
Section: Discussionmentioning
confidence: 99%